Peningkatan Kapasitas Kelompok Perhutanan Sosial Pascaperizinan HKm: Studi pada KTH Ake Guraci dan KTH Lestari Hutan Togafo - Andy Kurniawan; Buhari Umasugi; Meylinda Y Hanafi; Ramli Hadun; Adnan Sofyan; Aisjah Rachmawaty Ryadin (Universitas Pattimura, 2026)
Social forestry is a national policy instrument intended to improve community welfare while maintaining forest sustainability. However, the success of social forestry is shaped not only by the issuance of permits, but also by the post-permit capacity of farmer groups to manage institutions, enterprises, and forest areas. This study aims to analyze the institutional capacity of KTH Ake Guraci and KTH Lestari Hutan Togafo after obtaining Community Forestry (HKm) permits and to formulate strategies to strengthen their capacity. The study was conducted in the working area of the Ternate-Tidore Forest Management Unit using a descriptive approach with qualitative and quantitative data. SWOT analysis was applied through IFAS, EFAS, Internal-External (IE), and SWOT matrices. The results show that both groups are in the medium internal and external categories. KTH Ake Guraci recorded an IFAS score of 2.29 and an EFAS score of 2.26, while KTH Lestari Hutan Togafo recorded an IFAS score of 2.39 and an EFAS score of 2.35. Both groups occupy cell V of the IE matrix and quadrant I of the SWOT matrix, indicating that aggressive growth-oriented strategies remain feasible. Capacity strengthening should therefore focus on institutional consolidation, NTFP-based enterprise development, human resource improvement, and stronger facilitation, partnerships, and market access in the post-permit phase.